1989
DOI: 10.1007/bf01536059
|View full text |Cite
|
Sign up to set email alerts
|

Basal gastric acid secretion in nonulcer dyspepsia with or without duodenitis

Abstract: Nonulcer dyspepsia with or without duodenitis and duodenal ulcer disease are often considered to be a spectrum of the same acid-peptic process. Some reports evaluating basal gastric acid secretion in nonulcer dyspepsia and duodenal ulcer disease have supported that impression; however, results from different studies have been mixed. In order to compare basal gastric secretory profiles in nonulcer dyspepsia and duodenal ulcer disease, we determined basal acid outputs in 66 consecutive patients with the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 13 publications
1
30
0
2
Order By: Relevance
“…This has been, however, an inconsistent finding in different clinical studies [1]. In general, basal gastric acid secretion in patients with functional dyspepsia has been reported to be similar to that in asymptomatic controls but significantly lower than that in patients with duodenal ulcer [2,3]. Similar results have been found with regard to stimulated gastric acid secretion [3].…”
Section: Targeting the Abnormalities Of Gastric Acid Secretionsupporting
confidence: 70%
“…This has been, however, an inconsistent finding in different clinical studies [1]. In general, basal gastric acid secretion in patients with functional dyspepsia has been reported to be similar to that in asymptomatic controls but significantly lower than that in patients with duodenal ulcer [2,3]. Similar results have been found with regard to stimulated gastric acid secretion [3].…”
Section: Targeting the Abnormalities Of Gastric Acid Secretionsupporting
confidence: 70%
“…Although we did not quantify gastric acid secretion, exaggerated gastric acid secretion seems less likely. Previous studies have shown normal gastric acid secretion in FD patients (25,26), and we excluded patients with recent use of acid suppressive drugs to avoid rebound acid hypersecretion (27,28). H. pylori infection may increase gastric acid secretion, but all our patients were H. pylori negative.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth group of patients do not fall into any subgroup and are classified as unspecified (6). There has been support for the role of acid in the etiology of NUD even though the basal and peak acid secretion have been shown to be normal (7). The results of studies with acid suppressants have been conflicting (2,8,9) whereas studies with antacids have been universally negative (8)(9)(10)(11).…”
mentioning
confidence: 99%